2011
DOI: 10.1097/mpa.0b013e31820b4b23
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acid Inhibits Glucose-Stimulated Insulin Secretion Via the G Protein-Coupled Receptor PUMA-G in Murine Islet β Cells

Abstract: The results indicated that PUMA-G stimulation by NA in islet β cells inhibited GSIS likely via activation of the Gi signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…One possible explanation for the virtual absence of an insulin rebound in this situation is that NiAc inhibits insulin secretion. Indeed, NiAc-induced blunting of glucose-stimulated insulin secretion has been demonstrated in vitro (36,37), albeit at considerably higher NiAc concentrations than those achieved in the present study. Thus, timing gradual NiAc withdrawal to the fed state should minimize FFA rebound.…”
Section: Damage Control By Minimizing Ffa Reboundcontrasting
confidence: 40%
See 1 more Smart Citation
“…One possible explanation for the virtual absence of an insulin rebound in this situation is that NiAc inhibits insulin secretion. Indeed, NiAc-induced blunting of glucose-stimulated insulin secretion has been demonstrated in vitro (36,37), albeit at considerably higher NiAc concentrations than those achieved in the present study. Thus, timing gradual NiAc withdrawal to the fed state should minimize FFA rebound.…”
Section: Damage Control By Minimizing Ffa Reboundcontrasting
confidence: 40%
“…Second, excessive exposures can invoke additional complicating mechanisms beyond FFA lowering. Examples include hepatic DGAT2 inhibition with an IC 50 of 100 µM (13,35), suppression of glucose-mediated insulin secretion via direct activation of GPR109A in the islet observed at 100 µM (36,37), downregulation of phophodiesterase-3B in adipose tissue reported at an 10-fold higher dose of NiAc than used in the current study (9) but not occurring at the present dose level (10), and Toll-like receptor-4 signaling inhibition (38) observed at 100 µM. the potential for FFA lowering might in theory be greater in the fasting state, it has been suggested that antilipolysis in this situation may invoke a more powerful counter-regulatory response to defend the supply of the predominant oxidative fuel (20,30).…”
Section: Discussionmentioning
confidence: 99%
“…However, our data demonstrated that treatment with niacin led to a significant improvement in insulin resistance in HFD‐fed obese mice (HOMA‐IR). GPR109A has been shown to be functionally expressed in both human and murine islet β‐cells (72, 73). Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Invokes apoptotic pathways in neutrophils and some cancer cells (e.g., breast and colon cancer). [ 12 , 46 , 71 73 ] …”
Section: Introductionmentioning
confidence: 99%